Defect-impurity complex induced long-range ferromagnetism in GaN nanowires - S Assa Aravindh; Iman S Roqan (Materials Research Express, 2015)
Present work investigates the structural, electronic and magnetic properties of Gd doped wurtzite GaN nanowires (NWs) oriented along the [0001] direction in presence of intrinsic defects by employing the GGA +  U approximation. We find that Ga vacancy (V _Ga ) exhibits lower formation energy compared to N vacancy. Further stabilization of point defects occurs due to the presence of Gd. The strength of ferromagnetism (FM) increases by additional positive charge induced by the V _Ga . Electronic structure analysis shows that V _Ga introduces defect levels in the band gap leading to ferromagnetic coupling due to the hybridization of the p states of the Ga and N atoms with the Gd d and f states. Ferromagnetic exchange coupling energy of 76.4 meV is obtained in presence of Gd-V _Ga complex; hence, the FM is largely determined by the cation vacancy-rare earth complex defects in GaN NWs.